EFFECTIVENESS AND EFFICIENCY ISSUES IN EDUCATIONAL FUND UTILIZATION: AN ANALYSIS OF SCHOOL FINANCIAL MANAGEMENT IMPLEMENTATION TO IMPROVE EDUCATIONAL SERVICE QUALITY - Esti Maharani Widyanti; Arim Irsyadulloh Albin Jaya (STKIP Pesisir Selatan, 2025)
This study aims to analyze the implementation of school financial management in relation to the effectiveness and efficiency of educational fund utilization and its contribution to improving the quality of educational services. This study is motivated by the increasing demands for accountability and transparency in public financial management within the education sector, which position schools as strategic units responsible for ensuring that educational funds are managed in a targeted manner and oriented toward core educational services. However, in practice, many schools continue to face challenges in aligning financial planning, implementation, and supervision with learning priorities, resulting in the suboptimal impact of fund utilization on the quality of educational services. This study employs a qualitative approach with a case study design to obtain an in-depth and contextual understanding of the phenomenon under investigation. Data analysis was conducted using an interactive model consisting of data reduction, data display, and continuous conclusion drawing. The findings indicate that effective and efficient financial management is reflected in transparent and participatory budget planning, needs-based allocation of funds focused on core educational services, timely financial reporting, and consistent supervision.